2017
DOI: 10.18632/oncotarget.22629
|View full text |Cite
|
Sign up to set email alerts
|

RA and ω-3 PUFA co-treatment activates autophagy in cancer cells

Abstract: Retinoic acid (RA), is a promising therapeutic agent for the treatment of breast cancer. However, metabolic disorders and drug resistance reduce the efficacy of RA. In this study, we found that RA and ω-3 polyunsaturated fatty acids (ω-3 PUFAs) synergistically induced cell death in vitro and in vivo and autophagy activation. Moreover, RA-induced hypercholesterolemia was completely corrected by ω-3 PUFA supplementation. In addition, we demonstrated that the effects of this combination on the autophagic flux wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…Many studies investigating the role of cannabinoids and n-6 endocannabinoids in inhibiting cancer cell proliferation suggested involvement of the MAP kinase family of signal transducers [14,15,[33][34][35][36]]. Our findings generally demonstrated that both n-3 LCPUFA and their respective n-3 endocannabinoids can also elicit changes in MAPK signalling by decreasing expression of p38 MAPK and levels of activated (phosphorylated) p38 MAPK (pp38) in BC cells.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Many studies investigating the role of cannabinoids and n-6 endocannabinoids in inhibiting cancer cell proliferation suggested involvement of the MAP kinase family of signal transducers [14,15,[33][34][35][36]]. Our findings generally demonstrated that both n-3 LCPUFA and their respective n-3 endocannabinoids can also elicit changes in MAPK signalling by decreasing expression of p38 MAPK and levels of activated (phosphorylated) p38 MAPK (pp38) in BC cells.…”
Section: Discussionsupporting
confidence: 72%
“…In the case of EPA treatment, phosphorylated (activated) pp38 was significantly reduced, even though non-phosphorylated p38 levels were increased. Activation of p38 MAPK by cannabinoids has been reported previously [16,17,[34][35][36][37] and it is usually thought this activation leads to increased apoptosis, but here we show down-regulation of both total p38 MAPK and activated pp38 by n-3 LCPUFA and to depend on the stimuli, cell type, and/or the particular enzyme isoforms present (reviewed in [38]). In the current study we did not determine the latter.…”
Section: Discussionsupporting
confidence: 67%
“…CQ can inhibit the degradation of autophagosomes to inhibit the occurrence of autophagy. [22] Therefore, after adding CQ, the autophagosomes can aggregate in the cells, and the positive rate of MDC will be increased. As shown in Figure 8b, c, ZX-42 enhanced the amount of autophagosomes in a dose-dependent manner, and the autophagy inhibitor CQ increased the production of autophagosomes.…”
Section: Autophagy Plays a Protective Role In Zx-42induced Apoptosismentioning
confidence: 99%
“…Moreover, PA-induced abnormal glucose metabolism through a GPR120/P-p38 MAPK/KLF15 signal pathway in 3T3-L1 adipocytes, while GPR40 had no effects on P-p38 MAPK under PA stimulation. Interestingly but inconsistently, it has been reported that Gq-p38 activation was mediated by GPR40 rather than GPR120 involving in autophagy of breast cancer cells [28] . Probably, the activation mechanism of p38 MAPK may be distinct in different cell type or pattern.…”
Section: Discussionmentioning
confidence: 97%